Feedback training induces a bias for detecting happiness or fear in facial expressions that generalises to a novel task. Issue 3 (30th December 2015) - Griffiths, Sarah; Jarrold, Chris; Penton-Voak, Ian S.; Munafò, Marcus R.
Abstract: Many psychological disorders are characterised by insensitivities or biases in the processing of subtle facial expressions of emotion. Training using expression morph sequences which vary the intensity of expressions may be able to address such deficits. In the current study participants were shown expressions from either happy or fearful intensity morph sequences, and trained to detect the target emotion (e.g., happy in the happy sequence) as being present in low intensity expressions. Training transfer was tested using a six alternative forced choice emotion labelling task with varying intensity expressions, which participants completed before and after training. Training increased false alarms for the target emotion in the transfer task. Hit rate for the target emotion did not increase once adjustment was made for the increase in false alarms. This suggests that training causes a bias for detecting the target emotion which generalises outside of the training task. However it does not increase accuracy for detecting the target emotion. The results are discussed in terms of the training's utility in addressing different types of emotion processing deficits in psychological disorders. Highlights: Participants were trained to detect happiness or fear in low intensity expressions. Training lead to a bias for recognizing happiness or fear on faces in a novel task. However, participants did not become more accurate at recognizing happiness or fear. This training may be effective in altering specific biases in emotion recognition.